Analysis of LNG Cargo Loading Operations on Board PGN FSRU Lampung to Prevent Shipboard Accidents - Achmad Bashori; Suhartini; Innayaturrobbany; Asman Ala (Meteor STIP Marunda, 2025)
Liquefied Natural Gas (LNG) is one of the most actively developed energy resources due to its efficiency, relatively clean combustion characteristics, and suitability for large-scale transportation. LNG is produced by cooling natural gas to cryogenic temperatures of approximately −160°C (−260°F) at atmospheric pressure, converting it into a clear, colourless, and non-toxic liquid. The liquefaction process significantly reduces the volume of natural gas, achieving a volume reduction ratio of approximately 1:600, thereby improving the efficiency of LNG storage and transportation. The primary component of LNG is methane, with smaller proportions of ethane, propane, butane, pentane, and nitrogen. Despite its advantages as an energy source, LNG is classified as a hazardous cargo under international maritime regulations and requires specialised knowledge, technical competence, and strict operational procedures during handling and transportation. LNG carriers and Floating Storage and Regasification Units (FSRUs) are designed according to stringent safety requirements, including the standards established by the International Code for the Construction and Equipment of Ships Carrying Liquefied Gases in Bulk (IGC Code). This study aims to analyse LNG cargo loading operations on board PGN FSRU Lampung and identify measures to prevent operational failures and shipboard accidents during the ship-to-ship cargo transfer process. A qualitative descriptive research approach was employed, incorporating observations, interviews, and documentation analysis to evaluate cargo handling procedures, tank pressure management, and the utilisation of LNG control systems. The findings indicate that maintaining safe and efficient LNG loading operations requires optimal management of cargo tank pressure through effective utilisation of available control systems, particularly the Gas Combustion Unit (GCU) and Boil-Off Gas (BOG) recondenser. Insufficient utilisation of these systems may lead to ineffective pressure control, operational delays, and increased safety risks during cargo transfer activities. The study concludes that improving crew competency, strengthening adherence to LNG cargo handling procedures, and optimising the operation of pressure management equipment are essential to ensuring safe, efficient, and reliable ship-to-ship LNG transfer operations. The results provide valuable recommendations for improving LNG cargo management practices and reducing the risk of accidents during FSRU operations.